What is the effect of 19 years of restoration managements on soil and vegetation on formerly improved upland grassland? - Pavlů, Lenka; Pavlů, Vilém V; Fraser, Mariecia D (The Science of the total environment, 2021)
Finding the best management strategies to restore grassland diversity and achieve a compromise between agricultural use and biodiversity protection is a global challenge. This paper reports novel data relating to the impacts of 19 years of restoration managements predicted to increase botanical diversity within reseeded upland temperate grassland common in less favoured areas in Europe. The treatments imposed were: continuous sheep grazing, with and without lime application; hay cutting only, with and without lime application; hay cutting followed by aftermath grazing, with and without lime application; and a control treatment continuing the previous site management (liming, NPK application and continuous sheep grazing). Defoliation type, irrespective of liming, was the key driver influencing plant species diversity (hay cutting followed by aftermath grazing > hay cutting > grazing). Grazing only managements supported grasses at the expense of forbs, and thus related plant species diversity significantly declined. Limed treatments had higher concentrations of Ca and Mg in the soil compared to those receiving no lime. However, no effects on species richness or plant species composition were found. Potassium was the only element whose plant-available concentration in the soil tended to decrease in response to cutting treatments with herbage removal. Postponing the first defoliation to the middle of the growing season enables forbs to reach seed production, and this was the most effective restoration management option for upland grassland (as hay cutting only, and as hay cut followed by aftermath grazing). Although continuous low-density sheep grazing is often adopted as a means of improving floristic biodiversity, deleterious effects of this on plant diversity mean that it cannot be recommended as a means of long-term maintenance or restoration management of European temperate grasslands.
Keywords: Grassland; Restoration; Sheep; Cutting; lipnicovité; Grazing; půda; Europe; zvířata; Nutrients; biodiverzita; Sward; Poaceae; Liming; Animals; Soil; pastviny; Species richness; Evropa; ovce; Biodiversity